Dietary Pattern and Metabolic Syndrome in Thai Adults - W. Aekplakorn; W. Satheannoppakao; P. Putwatana; S. Taneepanichskul; P. Kessomboon; V. Chongsuvivatwong; S. Chariyalertsak (Journal of Nutrition and Metabolism)
Objectives. To determine the dietary patterns of middle-aged Thais and their association with metabolic syndrome (MetS). Methods. The Thai National Health Examination Survey IV data of 5,872 participants aged ≥30–59 years were used. Dietary patterns were obtained by factor analysis and their associations with Mets were examined using multiple logistic regression. Results. Three major dietary patterns were identified. The first, meat pattern, was characterized by a high intake of red meat, processed meat, and fried food. The second, healthy pattern, equated to a high intake of beans, vegetables, wheat, and dairy products. The third, high carbohydrate pattern, had a high intake of glutinous rice, fermented fish, chili paste, and bamboo shoots. Respondents with a healthy pattern were more likely to be female, higher educated, and urban residents. The carbohydrate pattern was more common in the northeast and rural areas. Compared with the lowest quartile, the highest quartile of carbohydrate pattern was associated with MetS (adjusted odds ratio: 1.82; 95% CI 1.31, 2.55 in men and 1.60; 95% CI 1.24, 2.08 in women), particularly among those with a low level of leisure time physical activity (LTPA). Conclusion. The carbohydrate pattern with low level of LTPA increased the odds of MetS.